Effectiveness of supervised implementation of an oral health care protocol on ventilator-associated pneumonia patients in intensive care units: a double-blind multicenter randomized controlled trial - Sharare Karimi; Ensi Kolyaei; Pooya Karimi; Khaled Rahmani (Elsevier, 2023)
Summary: Background: The available scientific evidence suggests a significant association between oral bacteria and the incidence of ventilator-associated pneumonia (VAP). Aims: The aim of this study was to determine the effectiveness of an oral health protocol in the prevention of ventilator-associated pneumonia. Methods: In this multi-center RCT, conducted in the intensive care units of neurological patients in three general teaching hospitals of two provinces located in the west of the Iran, a consecutive sample of 200 intubated patients were initially recruited. Patients were randomly allocated to the intervention (received oral health care based on evidence-based oral health protocol) or control (routine oral health care) groups. Both groups received their prescribed treatment regimen for seven consecutive days. The percentage of VAP diagnoses as main outcome assessed using clinical pulmonary infection score (CPIS). Findings: The rate of VAP in the intervention and control groups was 5% and 64%, respectively. The intervention reduced the risk of VAP by 97% and this difference was statistically significant (P <0.001). The chance of VAP occurrence in patients with lower levels of consciousness in univariate and multivariate analysis was significantly higher (OR: 2.38; 95%CI: 1.11-5.26) P <0.05). Conclusion: The results of our study suggest that the use of a dynamic supervised oral health care guideline is more effective than the routinely used protocols in the intensive care units of hospitals.